DEVELOPMENT STRATEGY FOR COFFEE AGROTOURISM IN KUBU RAYA DISTRICT - Ismawati Ismawati; Eva Dolorosa; Shenny Oktoriana (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2022)
The problems faced by the group of young skippers group in realizing coffee plantations agro-tourism include not analyzing the potential of agro-tourism based on the 4A concept and the absence of a coffee plantation agro-tourism development strategy. This study aims to identify and analyze the potential for coffee plantation agro-tourism development based on the 4A concept, as well as developing a strategy for developing coffee plantations in Kubu Raya Regency. The research location is in Punggur Kecil Village, Sungai Kakap District, Kubu Raya Regency. The study started from August to December 2021. The primary data collection method was carried out by distributing questionnaires to respondents consisting of the Kubu Raya Regency tourism, culture and sports office, agricultural extension workers, village officials, visitors, coffee farmers and coffee skipper youth groups. The process of determining the strategy is carried out through the EFAS, IFAS, SWOT and QSPM matrices. The results show that the agro-tourism potential of coffee plantations is based on the 4A concept, namely attraction can be seen from the potential of plantations and natural potential. Sufficient accessibility and amenities available only in the from the parking area while other facilities are not yet available. Ancillary available in the form of Bank Kalbar ATM, Community Health Center and places of worship, from the SWOT analysis, describing alternative agro-tourism development strategies are in a position of the weakness-opportunity (WO) strategy, with the chosen strategy priority being strategy III. Attract investors to cooperate in building tourist facilities that are not yet available.